Protocol for a scoping review of the qualitative literature on Indigenous infant feeding experiences - Anthony J Hanley; Hiliary Monteith; Tracey Galloway (BMJ Open)
Introduction Prudent infant nutrition, including exclusive breastfeeding to 6 months, is essential for optimal short-term and long-term health. Quantitative research to date has documented that many Indigenous communities have lower breastfeeding rates than the general population and that this gap in breastfeeding initiation and maintenance may have an important impact on chronic disease risk later in life. However, there are critical knowledge gaps in the literature regarding factors that influence infant feeding decisions. Qualitative research on infant feeding experiences provides a broader understanding of the challenges that Indigenous caregivers encounter, and insights provided by this approach are essential to identify research gaps, community engagement strategies, and programme and policy development. The objective of this review is to summarise the qualitative literature that describes breastfeeding and other infant feeding experiences of Indigenous caregivers.Methods and analysis This scoping review will follow guidelines from Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews, the Joanna Briggs Institute and the methodological framework from Arksey and O’Malley. In October 2020, we will conduct an electronic database search using Medline, Embase, The Cumulative Index to Nursing & Allied Health Literature (CINAHL), PsycINFO, and Scopus, and will focus on qualitative studies. Publications that have a focus on infant feeding in Canada, the USA, Australia and New Zealand, and the Indigenous caregiver experience from the caregiver perspective, will be included. We will conduct a grey literature search using Indigenous Studies Portal, country-specific browser searches, and known government, association, and community websites/reports. We will map themes and concepts of the publications, including study results and methodologies, to identify research gaps, future directions, challenges and best practices in this topic area.Ethics and dissemination Ethical approval is not required for this review as no unpublished primary data will be included. The results of this review will be shared through peer-reviewed publications and conference presentations. This protocol is registered through the Open Science Framework (osf.io/4su79).